Incidence of central precocious puberty more than doubled during COVID-19 pandemic: Single-center retrospective review in the United States - Trujillo, Marcela Vargas; Rungvivatjarus, Tiranun; Klein, Karen O. (Frontiers in Pediatrics, 2022)
Background and aim of the study: The frequency of new visits for early puberty increased during the Covid-19 pandemic in our pediatric endocrinology clinic at Rady Children’s Hospital in San Diego, CA, US. A few recent studies have shown an increase in the frequency of Central Precocious Puberty (CPP) in other centers during this pandemic. We conducted this study to evaluate the change in incidence of new CPP cases requiring treatment with GnRH agonist (GnRHa) in our clinic during the Covid-19 pandemic and compared it to pre-pandemic years. Methods: We performed a retrospective comparison of the number of visits of children newly diagnosed with CPP treated with GnRHa during the Covid-19 pandemic (5/2020–4/2021) and before the pandemic (5/2018-4/2019). We evaluated clinical and bone maturation data as well as differences in timing from diagnosis to onset of treatment. We evaluated the incidence of CPP requiring treatment for 5 years prior to the pandemic to evaluate for trends over time. Results: A total of 92 subjects were included. During pre-Covid year, 28 children (1 boy, 27 girls) were treated with GnRHa for CPP out of 2,340 new endocrinology visits (1.2% of patients seen). During Covid-19 year, 64 children (7 boys, 57 girls) were treated out of 2,261 new visits (2.8%). The incidence of new CPP cases requiring GnRHa during the pandemic more than doubled compared to pre-pandemic. Age at onset of treatment, degree of bone age (BA) advancement, time from diagnosis to onset of treatment, and changes in BMI during the pandemic were not different from pre-pandemic. Conclusions: CPP cases requiring GnRHa treatment significantly increased during the first year of the Covid-19 pandemic. This was not related to increased BMI or delay in onset of treatment. Age at diagnosis, degree of bone age advancement, and time from diagnosis to onset of treatment were all similar during the first year of the pandemic compared to the prior year.